Hubungan Penggunaan Gadget Terhadap Konsentrasi Belajar Pada Anak Usia Sekolah - Muthmainnah Asmal (PT. Hasba Edukasi Mandiri, 2025)
The use of gadgets has become an integral part of school-aged children’s lives in today’s digital era. This study aims to analyze the relationship between gadget usage and students’ concentration levels. The research employs a quantitative approach with a correlational method, involving 37 fifth-grade students from SD Inpres Maccini Makassar as the sample. Data were collected using a Likert scale questionnaire and analyzed using simple regression. Based on the analysis results or hypothesis testing, it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This means there is a significant relationship between the variable of gadget usage and learning concentration. From the regression analysis, the regression equation obtained is 5.214−0.413X This equation indicates that each one-unit increase in the gadget usage score will decrease the learning concentration score by 0.413. In other words, the longer the duration of gadget usage, the lower the concentration level in school-aged children.